How proteases from Enterococcus faecalis contribute to its resistance to short α-helical antimicrobial peptides - Nešuta, Ondrej; Budešínský, Miloš; Hadravová, Romana; Monincová, Lenka; Humpolicková, Jana; Cerovský, Václav (Pathogens and disease, 2017)
HYL-20 (GILSSLWKKLKKIIAK-NH2) is an analogue of a natural antimicrobial peptide (AMP) previously isolated from the venom of wild bee. We examined its antimicrobial activity against three strains of Enterococcus faecalis while focusing on its susceptibility to proteolytic degradation by two known proteases-gelatinase (GelE) and serine protease (SprE)-which are secreted by these bacterial strains. We found that HYL-20 was primarily deamidated at its C-terminal which made the peptide susceptible to consecutive intramolecular cleavage by GelE. Further study utilising 1,10-phenanthroline, a specific GelE inhibitor and analogous peptide with D-Lys at its C-terminus (HYL-20k) revealed that the C-terminal deamidation of HYL-20 is attributed to not yet unidentified protease which also cleaves internal peptide bonds of AMPs. In contrast to published data, participation of SprE in the protective mechanism of E. faecalis against AMPs was not proved. The resistance of HYL-20k to C-terminal deamidation and subsequent intramolecular cleavage has resulted in increased antimicrobial activity against E. faecalis grown in planktonic and biofilm form when compared to HYL-20.
Keywords: kationické antimikrobiální peptidy; Microbial Sensitivity Tests; Enterococcus faecalis; Amino Acid Substitution; Proteolysis; Serine Endopeptidases; vztahy mezi strukturou a aktivitou; Structure-Activity Relationship; Biofilms; mikrobiální testy citlivosti; C-terminal deamidation; antibakteriální látky; zvířata; želatinasy; včely; bakteriální proteiny; proteolýza; Antimicrobial Cationic Peptides; Amino Acid Sequence; Phenanthrolines; Anti-Bacterial Agents; serinové endopeptidasy; substituce aminokyselin; biofilmy; Bees; gelatinase; Bacterial Proteins; inhibitory enzymů; fenantroliny; plankton; Animals; Gelatinases; Plankton; antimicrobial peptides; Enzyme Inhibitors; biofilm; protease; sekvence aminokyselin